Financial Literization of MSMEs in Indonesia - Suci Damayanti, Endah; Haymans Manurung, Adler; Wahyu Hidayat, Wastam; Suroso, Sugeng (Dinasti Publisher, 2024)
The purpose of this journal is to analyze the level of financial literacy among MSMEs in Indonesia. Through surveys and interviews, this study tries to identify the main challenges faced by MSMEs in terms of financial management and formulate strategies to improve financial literacy among MSME players. Financial literacy plays a crucial role in improving the sustainability and competitiveness of MSMEs. This research proposes a holistic and integrated financial literacy strategy to strengthen the financial understanding of MSME players in Indonesia. I conducted this research to explain the idea of financial literacy among MSMEs in Indonesia. This research analyzes journal publications published in the last 5 years from 2016 to 2020 using a literature review using qualitative methods and descriptive statistics. It can be drawn from several journals. In conclusion, research on financial literacy shows an increasing trend from year to year. The research was conducted through a survey of a number of MSMEs in various economic sectors. Questions in the survey covered understanding of financial concepts, cash flow management and investment. In-depth interviews were also conducted to understand the first-hand experiences of MSME players. Low Literacy Level: All micro enterprises have a minimal level of financial literacy, especially in terms of preparing financial statements and long-term financial planning. The results show that many MSMEs lack understanding of financial basics, such as the preparation of simple financial statements and debt management. Therefore, efforts are needed to improve their financial literacy. Training and workshops: Organize regular training and workshops to provide an in-depth understanding of basic financial concepts. Establish an online platform with easily accessible financial education resources for MSME players. Collaboration with Financial Institutions: Strengthen collaboration with financial institutions to provide financial guidance and solutions that suit the needs of MSMEs.